Perancangan Balai Latihan Kerja Wanita Dengan Penerapan Arsitektur Kontemporer di Kalibata, Jakarta Selatan - Muhammad Azzam Robbani; Putri Suryandari; Dody Kurniawan (MAESTRO, 2023)
The Progres economic and trade developments have spurred changes in the structure of the economy and industry which will certainly affect the amount of manpower needed as human resources, standards and quality of labor need to be taken into consideration. over time now women can also participate in important components of economic development. Then came the design of women's work training centers to support national development efforts, especially development in the field of employment and skills for women.